Report of Five Years of Experience in Neonatal Screening for Mucopolysaccharidosis Type I and Review of the Literature - Vincenza Gragnaniello; Daniela Gueraldi; Laura Rubert; Francesca Manzoni; Chiara Cazzorla; Antonella Giuliani; Giulia Polo; Leonardo Salviati; Alberto Burlina (International Journal of Neonatal Screening, 2020)
Mucopolysaccharidosis type I (MPS I) is a progressive lysosomal storage disease, with neurological and visceral involvement, in which early diagnosis through newborn screening (NBS) and early treatment can improve outcomes. We present our first 5 years of experience with laboratory and clinical management of NBS for MPS I. Since 2015, we have screened 160,011 newborns by measuring α-L-iduronidase (IDUA) activity and, since 2019, glycosaminoglycans (GAGs) in dried blood spot (DBS) as a second-tier test. Positive screening patients were referred to our clinic for confirmatory clinical and molecular testing. We found two patients affected by MPS I (incidence of 1:80,005). Before the introduction of second-tier testing, we found a high rate of false-positives due to pseudodeficiency. With GAG analysis in DBS as a second-tier test, no false-positive newborns were referred to our clinic. The confirmed patients were early treated with enzyme replacement therapy and bone-marrow transplantation. For both, the clinical outcome of the disease is in the normal range. Our experience confirms that NBS for MPS I is feasible and effective, along with the need to include GAG assay as a second-tier test. Follow-up of the two positive cases identified confirms the importance of early diagnosis through NBS and early treatment to improve the outcome of these patients.